Pseudo-haptics Interfaces for robotic teleoperation - Xavier, R. (2024)
When remotely operating robotic systems, the situation awareness and the absence of the possibility of direct human touch in such a remote environment constitute major challenges in telerobotics. Haptic feedback has been playing an important role when people interact with remote environments (e.g., in robotic teleoperation) or provide more immersive experiences in virtual environments. Like haptic devices, pseudo-haptic techniques aim to simulate haptic sensations in human–computer interaction between real and remote or virtual worlds, by exploring multimodal feedback, mainly the visual, and the brain’s capabilities and limitations, without needing a haptic device to be attached or applied to the body. The authors discuss the possibility of exploring pseudo-haptic techniques, notably combined multimodal techniques, to improve robotic teleoperation, in remote vehicle driving, object maneuvering, situation awareness, and collaborative tasks, which as per the best authors’ knowledge has not been explored in the literature.